Are Turkish Videos About Geriatric Exercise Program Appropriate and Does YouTube Provide Reliable and Quality Information? - Mustafa Tuna; Hatice Ağır (Galenos Yayinevi, 2023)
Objective: The aim of this study was to investigate the safety and quality of Turkish videos about the provincial age exercise program on YouTube. Materials and Methods: On August 22, 2022, an internet search was made using YouTube, the popular search engine in Turkey, and the exercises recommended for the ages were evaluated. Forty YouTube videos were rated by two supervisors (physiatrists). The videos included in the study were evaluated using the Quality Criteria for Consumer Health Information (DISCERN) tool and Global Quality and Services (GQS) benchmarks. In addition, video duration, likes, dislikes, number of comments, duration of the video on the internet, video power index, viewing rate and liking rates were evaluated. Results: According to the evaluation of both observers, the videos were found to be of medium to poor quality. While the average DISCERN score of the first observer was 41.3±17.5, the average of the DISCERN score of the second observer was 44.2±17.1, and according to the analysis, the intraclass correlation coefficient value was found to be 0.898 and it was seen that there was a very good agreement. There was a high level of agreement between the two observers in terms of the DISCERN score category (κ=0.683, p<0.001). Again, according to both observers, GQS average of the videos was determined as moderate-poor results and positive correlation was found between both. Conclusion: It was determined that the content of the videos on YouTube about the age exercise programs was generally inadequate or of poor quality. It has been determined that there is a need for videos that can contribute to the preparation of higher quality and informational videos based on international guidelines, and to increase public awareness about patient compliance and exercise programs.